Research of physical-mechanical properties of superficial layer of billows, running rollers / B.I. Butakov, D.D. Marchenko, V.A. Artyukh, A.V. Zubekhina // Problems of Tribology. – 2012. – № 1. – Р. 83-94. - Бутаков, Б.И.; Марченко, Д.Д.; Артюх, В.А.; Зубехина, А.В. (Problems of Tribology, 2014)
The results of studies of physical and mechanical properties of the surface layer and an electron-diffraction studies of the microstructure of shafts, after hardening their surface plastic deformation with running rollers. The calculation of the depth of hardening, as measured by a change in proof stress, using regression analysis. The mechanism of dislocation cell structure in the grains due to the dislocation density after running.